THE DEVELOPMENT OF MOTION GRAPHIC ON COMPUTATIONAL THINKING WITH USING PROBLEM-BASED LEARNING TO ENHANCE ABILITY OF SOLVING PROBLEMS AND COLLABORATING OF MATHAYOMSUKSA TWO STUDENTS - Wiengpraprok, Yosathorn; Siripipattanakoon , Sutithep; Diteeyont, Watsatree (Journal of Educational Review Faculty of Education in MCU, 2025)
The purposes of this research were 1) To develop Motion graphic on computational thinking 2) To compare the pretest and posttest results on computational thinking 3) To study the ability of solving problems after being taught with Motion graphic on computational thinking 4) To study the ability of students’ collaboration after being taught Motion graphics on computational thinking and 5) To study students’ satisfaction towards using Motion graphic on computational thinking to enhance the ability of solving problems and collaborating as a teamwork. This is an experimental research. The population used in this research is 664 Mathayom 2 students, with a sample of 36 people in 1 classroom by cluster sampling. The research instruments are: a lesson plan with motion graphics, motion graphics media on computational thinking, a pre-test and an achievement test, a problem-solving ability test, a self-evaluation of teamwork ability, a satisfaction questionnaire, and data analysis using percentages, means, standard deviations, and a t-test for one sample. The results were as follow: 1) Motion graphic quality evaluation was 82.41/82.22 2) The students’ posttest were higher than before being taught at 0.01 level of statistical significance 3) The students’ ability of solving problems was higher than 75 percent criterion 4) The students’ ability of collaboration after being taught was higher than before being taught at 0.01 level of statistical significance and 5) The students’ satisfaction to Motion graphic on computational thinking with using problem-based learning was at the highest level.